Re-Examining of The Turkish Crude Oil Import Demand with Multi-Structural Breaks Analysis in The Long Run Period - Yapraklı, Sevda; Kaplan, Fatih (International Journal of Energy Economics and Policy, 2015)
This study examines the Turkish crude oil import demand for the period of 1970-2013. Unlike earlier studies on Turkey, we tested the income and price elasticities of crude oil demand with structual breaks. In emprical analysis, the income and the price of crude oil used as a function of crude oil import demand. We employed Carrion-i-Silvestre et al. (2009) test for testing unit root, Maki (2012) cointegration test employed for testing for the existence of relationships. DOLS estimation employed for the estimating the long-run income and price elasticities. The empirical results show that the partial elasticities of crude oil import demand; income is (0.18) and crude oil is (-0.25). In the light of these results, it is said that income and price elasticities of demand for crude oil import in the long-run are inelastic. Furthermore, we used dummy varibale for testing internal and external crisses affetct. We conlcuded that the external crises had major impact on import oil demand on the contrary to internal crises in the long run. Keywords: Income elasticity; Price elasticicy; Structual Breaks JEL Classifications: C22; F10; F14